THE EFFECT OF SELF-EFFICACY AND SYSTEM QUALITY ON EFFECTIVENESS USER E-LEARNING ON STUDENT ECONOMY AND BUSINESS TADULAKO UNIVERSITY - Dea Reskita; Syahir Natsir; Niulu Putu Evvy Rossanty; Wiri Wirastuti (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of self-efficacy and system quality on the effectiveness of e-learning use in students. faculty of Economics and Business of Tadulako University. The study used an associative quantitative approach with a stratified random sampling technique on 230 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS version 30. The results showed that self-efficacy and system quality simultaneously had a positive and significant effect on effectiveness use e-learning (F = 252,963; Sig. = 0,000), with contribution of 69.0% (R Square = 0.690). Partially, self-efficacy has a positive and significant effect on the effectiveness of e-learning use (t = 14.471; Sig. = 0.000), as does system quality (t = 12.882; Sig. = 0.000), with self-efficacy as a relatively more dominant variable. The results of this study are expected to provide academic contributions in the development of educational management science and information systems, particularly regarding the use of e-learning in the learning process. In addition, this study is also expected to be a consideration for Tadulako University, especially the Faculty of Economics and Business, in improving quality e-learning system and strengthen student self-efficacy, so that the effectiveness of e-learning use can increase and support the improvement of the quality of learning and student learning outcomes.